Negative Refractive Index in an Inhomogeneously Broadened Four-Level Inverted-Y Atomic Medium - Bang Nguyen (IEEE, 2021)
In this paper, we present the study on negative refractive index in an inhomogeneously broadened four-level inverted-Y atomic medium based on electromagnetically induced transparency (EIT). The expressions of the relative permittivity and the relative permeability are derived under Doppler broadening. For this four-level system, we have found two frequency bands of negative refractive index in an optical region corresponding to two EIT windows. The influences of coupling and signal laser fields as well as temperature on frequency bands of negative refractive index are investigated. Our research can be convenient for experimental implementation with real atomic media under different temperatures.